New mutation in the TRIP4 gene associated with congenital muscular dystrophy Davignon–Chauveau type (clinical case) - T. V. Kozhanova; S. S. Zhilina; T. I. Mescheryakova; M. Yu. Shorina; I. F. Demenshin; G. G. Prokopiev; I. V. Kanivets; V. S. Suchorukov; P. L. Anufriev; T. I. Baranich; A. A. Kozina; A. G. Prityko (Нервно-мышечные болезни)
Congenital muscular dystrophies are heterogeneous groups of neuromuscular diseases leading to hypotonia, progressive muscle weakness and dystrophic or structural signs in muscle biopsy. At the present time, 34 genes associated with congenital muscular dystrophy have been described. The clinical case of a rare form of congenital muscular dystrophia associated with a homozygous mutation in the TRIP4 gene in a patient with respiratory failure requiring respiratory support, neurological symptoms, muscular hypotonia, and multiple congenital malformations of skeletal system is presented for the first time in Russia. The undescribed pathogenic homozygous variant of the nucleotide sequence in the TRIP4 gene (chr15:64686179, c.136C>T, p.Arg46Ter, 2 exon, NM_016213.4) was detected by whole exome sequencing. The mutation in the TRIP4 gene was validated by Sanger sequencing in a child and its origin was investigated. The mother and father of the girl are carriers of the heterozygous variant in the TRIP4 gene. Identification of the genetic cause of a rare form of neuromuscular disease is important for determining the tactics of patient management and medical and genetic counseling of the family, as well as clarifying the pathogenesis of a rare pathology.